Remote sensing of river habitat for salmon restoration - Chantal Giroux; Chantal Giroux; Jon Grant; Craig J. Brown; Jeffrey Barrell; Jeffrey Barrell (Frontiers in Remote Sensing, 2022)
Losses of river complexity and viable habitat has led to negative effects on Atlantic salmon. With the rapid population decline of Atlantic salmon, there has been an increase in river restoration and salmon reintroduction projects, and an understanding of substrate is a vital component in the restoration of these habitats. However, the isolation and/or inaccessibility of many of these rivers make the collection of this information challenging and expensive based on conventional survey approaches. This study looks at the feasibility and accuracy of conducting substrate analysis using low-cost uncrewed aerial vehicles (UAV) at seven transects through macroscale river habitat (riffles, runs and pools) on the Upper Salmon River located in Fundy National Park near Alma, New Brunswick, Canada. Using ArcGIS, a supervised classification was conducted separating the dry and submerged substrate for higher accuracy. An object-based image analysis was conducted in PCI for delineation of substrate size. Small ideal spawning substrate was found to be concentrated in slower flowing pools while large substrate was concentrated in faster flowing riffles. The substrate analysis was conducted with an accuracy of 79% for dry substrate and 86% for submerged substrate, demonstrating the potential of UAV use in salmon habitat analysis.